PENGARUH BELANJA DAERAH LANGSUNG TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR TAHUN 2010-2019 (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
This study aims to examine the effect of direct regional spending on economic growth in East Java Province. This study uses secondary data obtained from official websites such as BPS East Java Province, and the type of data used in this study is quantitative data. The analysis technique used is multiple linear regression analysis. The results of this study indicate that 1. Partially, personnel expenditure, goods, and services expenditure, and capital expenditure have no significant effect on economic growth with a significant value of the t-test of the employee expenditure variable of 0.337 (greater than 0.05), for a significant value of the t-test goods and services expenditure variable is 0.622 (greater than 0.05) and for the significant value of the t-test variable for capital expenditure is 0.717 (greater than 0.05). 2. Simultaneously, the effect of personnel expenditure, goods and service expenditure, and capital expenditure has no significant effect on economic growth in East Java Province, as evidenced by the significance value of the F test of 0.599 which is smaller than 0.05